Conservation concerns a guide for collectors and curators - Bachmann, Konstanze; Cooper-Hewitt Museum (Washington, D.C. Smithsonian Institution Press, 1992)
Written in accessible, nontechnical language, this book's twenty-three essays provide invaluable conservation guidelines for a variety of materials and media. Focusing also on proper storage techniques and environmental control, contributors offer information on emergency planning, disaster management, and identifying damages that may require professional treatment.
Foreword / Dianne Pilgrim -- Acknowledgments / Konstanze Bachmann -- Introduction / Konstanze Bachmann -- Principles of storage / Konstanze Bachmann, Rebecca Anne Rushfield -- Emergency planning / Mary W. Ballard -- Control of temperature and humidity in small collections / Ann Brooke Craddock -- Construction materials for storage and exhibition / Ann Brooke Craddock -- Storage of works on paper / Marjorie Shelley -- Warning signs: when works on paper require conservation / Marjorie Shelley -- Storage and care of photographs / Klaus B. Hendriks -- Warning signs: when photographs need conservation / Klaus B. Hendriks -- The preservation and storage of sound recordings / Klaus B. Hendriks -- Painting storage: a basic guideline / Kenneth S. Moser -- When is it time to call a paintings conservator? / Charles von Nostitz -- Storage of historic fabrics and costumes / Christine Giuntine -- Textile conservation / Patsy Orlofsky -- Warning signs: when textiles need conservation / Lucy A. Commoner -- Storage containers for textile collections / Lucy A. Commoner -- Storage of stone, ceramic, glass, and metal / Lynda A. Zycherman -- The care and conservation of metal artifacts / Elayne Grossbard -- Furniture conservation / Susan Klim -- Upholstery conservation / Kathryn Gill -- Preserving ethnographic objects / Carolyn L. Rose -- Care of folk art: the decorative surface / Valerie Reich Hunt -- Composite objects: materials and storage conditions / Valerie Reich Hunt.
Includes bibliographical references (pages 141-149)
Keywords: Museum conservation methods